A4_04 "Crimes of the Hot", Possible or Not? - Crosby, Matthew; Pearce, Rebecca; Buckland, Jools; James, Oliver (Physics Special Topics, 2017)
In this paper we investigate the feasibility of moving the Earth to reduce global warming in the manner depicted in the Futurama episode "Crimes of the Hot". We determined that using a chemical rocket with either ethanol or hydrogen as the fuel would not be viable, as atleast 6.11% of the mass of the Earth would have to be used as fuel.